Word Formation Processes of Registers Used in Football Banter Community Page: A Sociolinguistics Study - I Made Verdy Natha Biantara Putera; Putu Chrisma Dewi; Ni Luh Desy Suari Dewi (LPPM Universitas Dhyana Pura, 2023)
The study aims to identify the types of word formation processes of registers used in football banter community. This study was conducted by using descriptive qualitative research which are reading and documentation method. The data was taken from Facebook on the page of football banter community in the period of 2016 to 2022. The data was collected by register theory of Wardhaugh (2006) and analyzed by using the theory of Yule (2010) about word formation processes. The results of this study showed that there were 20 registers found in football banter community page. Based on the analysis, the 20 registers were categorized into 8 types of word formation processes with the result as follows: 4 data of borrowing; 3 data of coinage; 3 data of derivation; 1 data blending; 3 data of compounding; 3 data of acronym; 2 data of conversion; 1 data of multiple. The results showed that the most dominant type of word formation processes is borrowing process. Therefore, the forming of a new word especially register is always gone through a process of word formation processes.